Student Satisfaction Level Through the Implementation of Information System at Senior High School in Indonesia - Risna Herjayanti; Endry Setiawan; Azainil Azainil (Universitas Muhammadiyah Enrekang, 2024)
This study aims to evaluate the level of student satisfaction with the implementation of digital information systems through websites and Instagram at Senior High School 2 Berau and identify factors that contribute to student satisfaction or dissatisfaction. The method used was a quantitative survey with questionnaires distributed to 103 students from classes X and XI as respondents. The data obtained was analyzed descriptively to provide an overview of the students' level of satisfaction, as well as identify specific aspects that influence their perception of the school's information system. The findings showed that most respondents were satisfied with the information services provided by the school through the digital platform, with satisfaction levels reaching more than 98% in various aspects such as ease of access, flexibility of use, visual design, and responsiveness of social media admins. This indicates that the implemented digital information system has successfully met the needs of students in terms of accessing information that is fast, accurate, and easy to understand. The theoretical implications of this study support the literature that emphasizes the importance of technology integration in education to increase students' satisfaction and connectedness with school. Practically, the findings provide insights for other schools in optimizing the use of digital platforms as a means of communication and information delivery. However, this study has limitations in terms of respondent coverage which only includes one school, so further research with a wider coverage is needed to obtain more generalizable results.